Reference Intervals for Hematology and Clinical Chemistry for the African Elephant (Loxodonta africana) - Steyrer, Christine; Miller, Michele; Hewlett, Jennie; Buss, Peter; Hooijberg, Emma H. (Frontiers in Veterinary Science, 2021)
The African elephant (Loxodonta africana) is listed as vulnerable, with wild populations threatened by habitat loss and poaching. Clinical pathology is used to detect and monitor disease and injury, however existing reference interval (RI) studies for this species have been performed with outdated analytical methods, small sample sizes or using only managedcaptive animals. The aim of this study was to generate hematology and clinical chemistry RIs, using samples from the free-ranging elephant population in the Kruger National Park, South Africa. Hematology RIs were derived from EDTA whole blood samples automatically analyzsed (n=23)on the scil Vet abc or Horiba ABX Micro ESV60; manual PCV was measured from 48 samples; and differential cell count results (n=51) from 51 blood smear examinations were included. Clinical chemistry RIs were generated from the results of automated analyzseris on 50 stored serum samples (n=50) using the Abaxis VetScan VS2 (Large Animal rotor). Reference intervals were generated according to American Society for Veterinary Clinical Pathology guidelines with a strict exclusion of outliers. Hematology RIs were: PCV 34-49%, RBC 2.80-3.96 x1012/L, HGB 116-163 g/L, MCV 112-134 fL, MCH 35.5-45.2 pg, MCHC 314-364 g/L, PLT 182-386 x109/L, WBC 7.5-15.2 x109/L, segmented heterophils 1.5-4.0 x109/L, band heterophils 0.0-0.2 x109/L, total monocytes 3.6-7.6 x109/L (means for “regularnormal” were 35.2%, bilobed 8.6%, round 3.9% of total leukocytes), lymphocytes 1.1-5.5 x109/L, eosinophils 0.0-0.9 x109/L, basophils 0.0-0.1 x109/L. Clinical chemistry RIs were: albumin 41-55 g/L, ALP 30-122 U/L, AST 9-34 U/L, calcium 2.56-3.02 mmol/L, CK 85-322 U/L, GGT 7-16 U/L, globulin 30-59 g/L, magnesium 1.15-1.70 mmol/L, phosphorus 1.28-2.31 mmol/L, total protein 77-109 g/L, urea 1.2-4.6 mmol/L. Reference intervals were narrower than those reported in other studies. These RI will be helpful in the future management of injured or diseased elephants in national parks and zoological settings.